An analytical review on the annulment of Internal Security Act 1960 and its effects on the rise of firearm crimes in Malaysia / Nor 'Ain Karina Marzuki … [et al.] - Marzuki, Nor 'Ain Karina; Abdul Ghani, Hawa Hidayah; Ab. Rahman, Najwa; Ramli, Nurshahira (Faculty of Law, 2014)
The Internal Security Act 1960 which was originally used to combat communist invasion during the Emergency period had been used by the government to combat subversive action and organized violence against persons and property under Article 149 of the Federal Constitution. The law however has been replaced by the Security Offenses (Special Measures) Act 2012 due to concerns of infringement of human rights. Despite the existence of strict laws, crime rates continue to increase. In most situations, the weapons owned by the offenders were obtained illegally. Therefore, the questions that arise here are; whether the repeal of the ISA has undesirable effects to the security of the country, where there has been an increase in the crimes related to firearms between the abolishment of ISA and the introduction of SOSMA, and to compare preventive detention laws in Malaysia with Singapore and to find out steps to be taken to overcome the problems despite having stringent laws. This research study will focus on the efficiency of the law and enforcement of the authority. The abolishment of ISA will be analysed thoroughly to improve SOSMA. This research would also be helpful to legislators to evaluate the effectiveness of the strict law, specifically SOSMA, in order to determine whether this law truly protects public safety. To conclude, it is reasonable to examine the laws of SOSMA and ISA to improve Malaysia's preventive detention laws to protect Malaysia's national security and public order.